2014
DOI: 10.1016/j.apmr.2014.05.025
|View full text |Cite
|
Sign up to set email alerts
|

Investigating Measures of Intensity During a Structured Upper Limb Exercise Program in Stroke Rehabilitation: An Exploratory Study

Abstract: Objectives-To use three measures of intensity (i) time, (ii) observed repetitions and (iii) wrist accelerometer activity counts to describe the intensity of exercise carried out when completing a structured upper limb exercise programme. To explore if a relationship exists between wrist accelerometer activity counts and observed repetitions. Design-Observational study design. Setting-Rehabilitation centre research laboratory.Participants-Thirteen community dwelling stroke survivors with upper limb hemiparesis.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
39
0
4

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(46 citation statements)
references
References 30 publications
3
39
0
4
Order By: Relevance
“…Overall session duration may not be an accurate method of measuring intensity, as a one-hour intervention session may not involve one hour of practice. An observational study of 13 adults with stroke found that participants engaged in active practice for only 64% of total session time (Connell, McMahon, Simpson, Watkins, & Eng, 2014).…”
Section: High Intensity Practicementioning
confidence: 99%
“…Overall session duration may not be an accurate method of measuring intensity, as a one-hour intervention session may not involve one hour of practice. An observational study of 13 adults with stroke found that participants engaged in active practice for only 64% of total session time (Connell, McMahon, Simpson, Watkins, & Eng, 2014).…”
Section: High Intensity Practicementioning
confidence: 99%
“…Jedno mówi o 23, drugie o 32 powtórzeniach aktywności ruchowych kończyny górnej [30] w trakcie fizjoterapii i terapii zajęciowej [29]. W ostatnim czasie pojawiły się również dwa niezależne badania pokazujące, że pacjenci w fazie podostrej po udarze są w stanie w ciągu godzinnej fizjoterapii wykonać od 251 do 281 różnych aktywności ruchowych KG z niedowładem [31,32]. Nie odnotowano żadnych polskich badań mówiących o dawce terapeutycznej aktywnych zadaniowych ćwi-czeń KG, w tym ręki w postępowaniu fizjoterapeutycznym i terapii zajęciowej w okresie pierwszych czterech tygodni od udaru mózgu jak i w okresie późniejszym.…”
Section: Wczesna Rehabilitacja Po Udarze Mózgu a Fizjoterapia Chorychunclassified
“…However, new evidence indicates that post-stroke UL physi-na, gdy pacjent jest aktywnie zaangażowany w funkcjonalne zadania ruchowe (ang. Activity -related arm training) [31][32][33]35]. Za najbardziej obiecujące strategie we wczesnej fizjoterapii po udarze mózgu uważa się: zmodyfikowaną terapię ruchem wymuszonym koniecznością -ZTRWK (mCIMT-Modified Constraint-Induced Movement Therapy), terapię z zastosowaniem robotów, specyficzny powtarzalny trening zadaniowy (ang.…”
Section: Strategies Of Upper Limb Exercises and Early Physiotherapy Aunclassified
See 2 more Smart Citations